Evaluación de mezcla de cascarilla de arroz y barro como medio filtrante para remoción de sólidos suspendidos en agua de río. - Guzmán Paredes, Washington Agapo (2018)
The objective of this investigation was to evaluate the relationship between rice husk mixtures with mud as filter bed forms in the removal of suspended solids in river water. During the study two different forms of filter medium (discs and spheres) elaborated from the cooking of three mixtures of husk (C) + mud (B) (5%(C)+95%(B), 10%(C)+90%(B); 15%(C)+85%(B)) and four retention times (0,16; 1; 5; 12 and 24 hours), for the filtering process a structure was created to contain the filtering medium and to homogenize the retention times in the different treatments . The filtration process showed degrees of removal of suspended solids of less than 2%, with the lowest values being treatments 5 and 3 and the highest values in the target and treatments 1 and 7. In the statistical analysis of the mixtures used (Factor A) it was verified the existence of significant differences between the degrees of removal, being that the lowest degrees of removal were in mixture 1 (5% (C) + 95% (B) and the highest in the control filtration.) Regarding the forms under study (Factor B) by means of which the existence of significant differences between the degrees of removal was verified, the filter without the presence of filtering medium presented the highest degrees of removal and the discs the lowest degrees of removal, so it can be defined that the utilization of discs or spheres of the characteristics analyzed as filter media is not a reliable alternative for the removal of suspended solids in river wáter.